Variasi Kontaminasi Mikroplastik pada Kerang Dara (Anadara granosa) berdasarkan Ukuran Individu di Pasar Induk Jakabaring, Palembang - Syakira Nurrachman Fadillah; Beta Susanto Barus; Wike Ayu Eka Putri; Gusti Diansyah; Yulianto Suteja; Anna Ida Sunaryo Purwiyanto (JURNAL SAINS TEKNOLOGI & LINGKUNGAN, 2026)
Blood cockles (Anadara granosa) are filter-feeding bivalves that may accumulate microplastics and become a pathway of human exposure through seafood consumption. This study analyzed size-based variation in microplastic contamination in blood cockles marketed at Jakabaring Central Market, Palembang, Indonesia. Fifteen individuals were classified into three size groups: small (<3 cm), medium (3–4 cm), and large (>4 cm). Microplastics were extracted using 10% KOH digestion and identified microscopically according to abundance, shape, and color. The results showed a slight increase in abundance from 12.8 particles/individual in small cockles to 13.0 and 14.6 particles/individual in medium and large cockles, but the differences were not significant (p=0.467). Fragments were the dominant shape, while black particles predominated in all size groups. Pearson correlation indicated a weak positive relationship between soft tissue weight and microplastic abundance (r=0.360; p=0.188). These findings indicate that contamination is driven by pollution sources and environmental conditions rather than individual size.